2018
DOI: 10.1123/ijspp.2016-0793
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrate Supplementation on Cycling Performance in the Heat in Well-Trained Cyclists

Abstract: Three days of [Formula: see text] supplementation resulted in small increases in rectal temperature during low- to moderate-intensity exercise, but this did not appear to influence 4-km cycling time-trial performance in hot climates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…To support this observation, we found that individuals with lower aerobic fitness manifest a larger attenuation of blood pressure during exercise in a hot environment. Notwithstanding this novel observation, given that unstable and falling blood pressure can signal cardiovascular failure during exercise in the heat (Rowell 1974), our data suggest that ingesting NO 3 --rich BR prior to 324 exercising in the heat should be implemented with caution, particularly since its effect on exercise performance in a hot environment is currently controversial (Kent et al 2017;McQuillan et al 2017). While the potential ergogenic effects of BR supplementation appear to be inversely related to aerobic fitness (Porcelli et al 2015) and is recommended to enhance endurance performance in recreationally-active individuals in thermoneutral conditions (Jones 2014), BR supplement should be used with caution in hot environments to limit the potential for the development of excessive hypotension.…”
Section: Discusssionmentioning
confidence: 86%
“…To support this observation, we found that individuals with lower aerobic fitness manifest a larger attenuation of blood pressure during exercise in a hot environment. Notwithstanding this novel observation, given that unstable and falling blood pressure can signal cardiovascular failure during exercise in the heat (Rowell 1974), our data suggest that ingesting NO 3 --rich BR prior to 324 exercising in the heat should be implemented with caution, particularly since its effect on exercise performance in a hot environment is currently controversial (Kent et al 2017;McQuillan et al 2017). While the potential ergogenic effects of BR supplementation appear to be inversely related to aerobic fitness (Porcelli et al 2015) and is recommended to enhance endurance performance in recreationally-active individuals in thermoneutral conditions (Jones 2014), BR supplement should be used with caution in hot environments to limit the potential for the development of excessive hypotension.…”
Section: Discusssionmentioning
confidence: 86%
“…Following a moderate dose of inorganic dietary NO 3 − (8.3 mmol NO 3 − ·d − 1 ) for 6 days, Kuennen et al (2015) observed a reduced O 2 cost of a 45 min loaded march in a hot and humid environment compared to a PLA. Interestingly, it was shown that dietary NO 3 − supplementation increased subject’s T c , a finding that was later replicated during a 4 km cycling TT in hot conditions (McQuillan et al 2018). This may be due to elevated gastrointestinal blood perfusion, which may enhance thermal transfer during exercise in the heat.…”
Section: Introductionmentioning
confidence: 88%
“…Given that cutaneous vasodilation is critical for the maintenance of a stable core temperature ( T c ), the role of dietary NO 3 − supplementation in the heat warrants investigation. Indeed, the effect of dietary NO 3 − supplementation on exercise performance in heat has recently been investigated in one non-athletic population (Kuennen et al 2015) and in three studies of well-trained cyclists (Kent et al 2018a, b; McQuillan et al 2018). Following a moderate dose of inorganic dietary NO 3 − (8.3 mmol NO 3 − ·d − 1 ) for 6 days, Kuennen et al (2015) observed a reduced O 2 cost of a 45 min loaded march in a hot and humid environment compared to a PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, evidence is required to confirm whether benefits are observed in highly trained populations (who tend not to respond to NO supplementation), and to determine which NO precursors provide the most effective GI protection. A further practical consideration is the apparent impaired thermoregulation associated with reduced cutaneous vasodilation, which might disrupt the GI barrier especially when exercising in the heat [258,259].…”
Section: Nitric Oxidementioning
confidence: 99%